2022
DOI: 10.1249/mss.0000000000003107
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Responses to Passive and Active Movement in Premenopausal Females: Comparisons across Sex and Menstrual Cycle Phase

Abstract: Purpose: Adequate, robust vascular responses to passive and active movement represent two distinct components linked to normal, healthy cardiovascular function. Currently, limited research exists determining if these vascular responses are altered in premenopausal females (PMF) when compared across sex or menstrual cycle phase. Methods: Vascular responses to passive leg movement (PLM) and handgrip (HG) exercise were assessed in PMF (n = 21) and age-matched men (n = 21). A subset of PMF subjects (n = 11) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…The current ndings are novel and signi cant, however, only male subjects were included. Previous investigations have reported no sex-related differences in the hyperemic and vasodilatory response to PLM (59), thus the current ndings may be extrapolated to females as well. Therefore, future investigations including female are warranted to investigate how potential basal differences in MSNA between sex may impact the hyperemic and vasodilatory response to PLM as young males express greater MSNA compared to their female counterparts (60, 61).…”
Section: Experimental Considerationssupporting
confidence: 49%
“…The current ndings are novel and signi cant, however, only male subjects were included. Previous investigations have reported no sex-related differences in the hyperemic and vasodilatory response to PLM (59), thus the current ndings may be extrapolated to females as well. Therefore, future investigations including female are warranted to investigate how potential basal differences in MSNA between sex may impact the hyperemic and vasodilatory response to PLM as young males express greater MSNA compared to their female counterparts (60, 61).…”
Section: Experimental Considerationssupporting
confidence: 49%
“…To maximize the participation and adherence of those with PTSD, the study visits for females in the PTSD group were not confined to the early follicular phase of their menstrual cycles, as the female participants in the control group were. Previous studies have suggested that oestrogen has a favourable influence on vascular function (Baker et al, 2016;Limberg et al, 2010); however, work from our group (Weggen et al, 2023) and others (Restaino et al, 2022) has reported no significant alterations in VC, MAP and vascular reactivity during progressive handgrip exercise when evaluated between phases of the menstrual cycle. Although the PTSD group comprised the same participants who participated in a recently published study (Weggen et al, 2021), some differences did arise when data were contrasted with the prior publication.…”
Section: Experimental Limitationsmentioning
confidence: 57%
“…A RMANOVA was then utilized to determine potential interaction effects of the AO supplementation (vs. PL) within each group for VC, MAP and BF responses at the 3 and 6 kg workloads. Sample size was calculated based on prior literature published by our laboratory (Weggen et al., 2023) examining group differences in VC during handgrip exercise as well as prior literature reporting improvements in exercise‐induced BF and VC responses following acute AO supplementation in older adults (Carlson et al., 2008) and evaluated with two‐tail directionality at α = 0.05, power (1 − β) of 0.8, and effect size of 1.2 and 0.9, respectively, using SPSS Statistics 25.0 (IBM Corp., Armonk, NY, USA), which indicated a total of 12 participants would be required for this study. Normal data distribution was assessed via the Shapiro–Wilk test.…”
Section: Methodsmentioning
confidence: 99%